Prevention of doxorubicin-induced experimental cardiotoxicity by Nigella sativa in rats - Adiyaman, Mehmet Sahin; Adiyaman, Ozlem Aba; Dagli, Adile Ferda; Karahan, Mehmet Zulkif; Dagli, Mustafa Necati (Elsevier Espana Slu, 2022)
Introduction: Doxorubicin (DOX) is an anthracycline cytotoxic chemotherapeutic drug that is commonly used in cancer treatment. A major side effect limiting the clinical use of DOX is cardiotoxicity due to oxidative injury. Nigella sativa (NS) is an annual flowering plant with antioxidant properties. Its seeds contain several bioactive constituents such as saturated and unsaturated fatty acids, thymoquinone, dithymoquinone, thymohydroquinone, and thymol. In this study, we investigated the effect of NS extract on DOX-induced cardiotoxicity. Methods: The experimental study animals consisted of 28 male Sprague Dawley rats weighing between 300 and 400 g. Four study groups each of seven rats were defined: controls; NS extract; DOX; and DOX+NS. Control and DOX rats received standard food, while each rat in the NS and DOX+NS groups also received 100 mg/kg NS extract orally. At day 28 of follow-up, rats in the DOX groups were administered a single 10 mg/kg intraperitoneal dose of DOX, while rats in the control and NS groups received a single 10 mg/kg dose of physiological saline solution. All animals were monitored for 35 days. On day 35, the rats were decapitated and serum and cardiac tissue samples were obtained. Troponin and NT-proBNP levels were measured in blood sera, while malondialdehyde (MDA), nitric oxide, total antioxidant capacity (TAC), and total oxidative stress (TOS) levels were quantified in sera and tissue samples. Histological alterations that were assessed in cardiac tissue included myocyte disarray, small vessel disease, myocyte hypertrophy, and fibrosis. Results: The DOX group had significantly higher NT-proBNP, TOS, and MDA, with greater histopathological derangement. TAC was significantly elevated in the DOX+NS group, which also exhibited significantly lower troponin, TOS, and MDA, as well as significantly higher TAC com-pared to the DOX group. Histopathological examination showed that the significant structural derangement observed in DOX rats was markedly and significantly reduced in DOX+NS rats. Conclusion: Our results suggest that NS extract may prevent DOX-induced cardiotoxicity and thus represents a promising cardioprotective agent. (c) 2021 Sociedade Portuguesa de Cardiologia. Published by Elsevier Espana, S.L.U. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Prevenção da cardiotoxicidade da doxorrubicina pela Nigella sativa em ratos
Keywords: Nigella sativa; Thymoquinone; Doxorubicin; Oxidative stress; Cardiotoxicity